A PIF1/PIF3-HY5-BBX23 Transcription Factor Cascade Affects Photomorphogenesis . Issue 4 (7th July 2017) - Zhang, Xinyu; Huai, Junling; Shang, Fangfang; Xu, Gang; Tang, Weijiang; Jing, Yanjun; Lin, Rongcheng
Abstract : Two PIF transcription factors activate the expression of HY5 and BBX23, the proteins of which interact to affect downstream gene expression in photomorphogenesis. Abstract: Light signaling plays an essential role in controlling higher plants' early developmental process termed as photomorphogenesis. Transcriptional regulation is a vital mechanism that is orchestrated by transcription factors and other regulatory proteins working in concert to finely tune gene expression. Although many transcription factors/regulators have been characterized in the light-signaling pathway, their interregulation remains largely unknown. Here, we show that PHYTOCHROME-INTERACTING FACTOR3 (PIF3) and PIF1 transcription factors directly bind to the regulatory regions of ELONGATED HYPOCOTYL5 (HY5) and a B-box gene BBX23 and activate their expression in Arabidopsis ( Arabidopsis thaliana ). We found that BBX23 and its close homolog gene BBX22 play a redundant role in regulating hypocotyl growth, and that plants overexpressing BBX23 display reduced hypocotyl elongation under red, far-red, and blue light conditions. Intriguingly, BBX23 transcription is inhibited by light, whereas its protein is degraded in darkness. Furthermore, we demonstrate that HY5 physically interacts with BBX23, and these two proteins coordinately regulate the expression of both light-induced and light-repressed genes. BBX23 is also recruited to the promoter sequences of the light-responsive genes in a partial HY5-dependent manner. Taken together, our study reveals that the transcriptional cascade consisting of PIF1/PIF3, HY5, and BBX23 controls photomorphogenesis, providing a transcriptional regulatory layer by which plants fine-tune their growth in response to changing light environment.